2015
DOI: 10.1158/1055-9965.epi-14-0694-t
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prostate Cancer Risk Variants with Gene Expression in Normal and Tumor Tissue

Abstract: Background Numerous germline genetic variants are associated with prostate cancer risk, but their biological role is not well understood. One possibility is that these variants influence gene expression in prostate tissue. We therefore examined the association of prostate cancer risk variants with the expression of genes nearby and genome-wide. Methods We generated mRNA expression data for 20,254 genes with the Affymetrix GeneChip Human Gene 1.0 ST microarray from normal prostate (N=160) and prostate tumor (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 33 publications
3
102
0
Order By: Relevance
“…In the present study, we expected to prove that RNASEL, MSR1, KLK3, AR, and ELAC2 mRNA expression has a diagnostic value in patients with PCa by the exposed expression patterns in PCa in these genes [21]. Determining the biologic role of these variants-which would help better understanding PCa etiology-and identifying new targets for chemoprevention is essential [22].…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, we expected to prove that RNASEL, MSR1, KLK3, AR, and ELAC2 mRNA expression has a diagnostic value in patients with PCa by the exposed expression patterns in PCa in these genes [21]. Determining the biologic role of these variants-which would help better understanding PCa etiology-and identifying new targets for chemoprevention is essential [22].…”
Section: Discussionmentioning
confidence: 93%
“…lung cancer, meningiomas and breast cancer (Fevre-Montange, et al, 2009; Molina-Pinelo, et al, 2014; Pio, et al, 2010; Thakkar, et al, 2010). A very recent study found association of expression of MLPH (and some other genes) with nearby SNPs in prostate tissue (Penney, et al, 2015). In small lung cell cancer MLPH mRNA was identified as a target of differentially expressed miRNAs (Molina-Pinelo, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-transcriptome mRNA expression was available from a prior case–control study, including 404 men in PHS and HPFS with prostate cancer (14). The study design is described in detail in reference 14.…”
Section: Methodsmentioning
confidence: 99%